Comparison of Antiemetic Effects of Ondansetron, Granisetron and Tropisetron in Treatment of Acute Emesis Caused By Cisplatin/Paclitaxel Chemotherapy - Turan, Taner; Bozkurt, Ülkü; Boran, Nurettin; Özgül, Nejat; Karaçay, Özlem; Tulunay, Gökhan; Kög, İskender and Köse, Faruk (Gynecology Obstetrics & Reproductive Medicine, 2016)
OBJECTIVE: Emesis is significant side effect of chemotherapy. In this study we aimed to compare prophylactic effect of ondansetron (OND), granisetron (GRA) and tropisetron (TRO) on acute emesis induced by cisplatin/paclitaxel combine chemotherapy. STUDY DESIGN: Between years 1993 and 2005, 172 patients have been operated for gynecologic malignancy and who had first-line chemotherapy (cisplatin-paclitaxel) were evaluated retrospectively. Chemotherapy was started with paclitaxel (175 mg/m2, 3 hours infusion) followed by cisplatin (75 mg/m2, 2 hours infusion). Dexamethasone (24 mg) was given 60 min before chemotherapy and infused until chemotherapy. 5 HT3 antagonist (OND=8 mg/TRO = 5 mg/GRA=3 mg) is started 1 hour before chemotherapy and given in 30 minutes. The second dose of OND also was given before cisplatin (8 mg, 30 min infusion). Chemotherapy toxicity was assessed according to WHO criteria. According to this, grade 0 was accepted as a complete response while grade 1 and more toxicity were accepted as nonresponse. RESULTS: 172 patients received 968 chemotherapy courses. OND, TRO, GRA were given 23.8% of patients and 23.3% of courses, 16.7% of patients and 15.7% of courses, 60.5% of patients and 59.9% of courses, respectively. Grade 3 toxicity was developed in 3.5% of patients and 0.8% of courses. None of the patients developed grade 4 toxicity. Complete response occurred in 28.5% of patients and 63% of courses. If it has been evaluated only for courses GRA is more effectiv e than TRO. Other than there was no significant difference in antiemetic potency between the drugs for courses and patients. CONCLUSION: Although this study is not prospective, it is homogenous for treatment modalities and patient selection. Complete response was observed in 63% of courses; however this antiemetic affect is not found to be satisfactory. In order to develope better protocols there is need for prospective studies on homogenous group. Antiemetic efficiency has to associate for chemotherapy protocols.